2005
DOI: 10.1038/nn1570
|View full text |Cite
|
Sign up to set email alerts
|

K-ATP channels promote the differential degeneration of dopaminergic midbrain neurons

Abstract: The selective degeneration of dopaminergic (DA) midbrain neurons in the substantia nigra (SN) is a hallmark of Parkinson disease. DA neurons in the neighboring ventral tegmental area (VTA) are significantly less affected. The mechanisms for this differential vulnerability of DA neurons are unknown. We identified selective activation of ATP-sensitive potassium (K-ATP) channels as a potential mechanism. We show that in response to parkinsonism-inducing toxins, electrophysiological activity of SN DA neurons, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
283
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(314 citation statements)
references
References 48 publications
22
283
1
Order By: Relevance
“…Thus, mitoK ATP channels may be an important molecular target for inhibiting microglia-mediated neuroinflammation and for treating neuroinflammation-related neurodegenerative disorders. Although Liss et al (2005) reported that genetic inactivation of Kir6.2 resulted in a selective rescue of substantia nigra dopaminergic neurons in a MPTP model of dopaminergic degeneration, there were a large number of evidences for benefits afforded by activating mitoK ATP in ischemia and degeneration (Yamauchi et al, 2003;Busija et al, 2004;Farkas et al, 2005a, b). This discrepancy may be owing to the difference between the opening of mitoK ATP channels and genetic inactivation of Kir6.2.…”
Section: Iptakalim Inhibits Neuroinflammation F Zhou Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, mitoK ATP channels may be an important molecular target for inhibiting microglia-mediated neuroinflammation and for treating neuroinflammation-related neurodegenerative disorders. Although Liss et al (2005) reported that genetic inactivation of Kir6.2 resulted in a selective rescue of substantia nigra dopaminergic neurons in a MPTP model of dopaminergic degeneration, there were a large number of evidences for benefits afforded by activating mitoK ATP in ischemia and degeneration (Yamauchi et al, 2003;Busija et al, 2004;Farkas et al, 2005a, b). This discrepancy may be owing to the difference between the opening of mitoK ATP channels and genetic inactivation of Kir6.2.…”
Section: Iptakalim Inhibits Neuroinflammation F Zhou Et Almentioning
confidence: 99%
“…This discrepancy may be owing to the difference between the opening of mitoK ATP channels and genetic inactivation of Kir6.2. In addition, the K ATP channels in dopaminergic neurons composed of Kir6.2 and SUR1 subunits display a promotion of neurodegenerative process in PD (Liss et al, 2005;Deutch and Winder, 2006), but it is worth noting that the composing subunits of K ATP channels in microglia differ from that of dopaminergic neurons and may play a distinct role in the initiation and process in the degenerative diseases.…”
Section: Iptakalim Inhibits Neuroinflammation F Zhou Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of post-synaptic K ATP channels causes membrane hyperpolarization, which limits neuronal excess excitation; activation of presynaptic K ATP channels can directly modulate neurotransmitter release from nerve terminals. Therefore, K ATP channel openers (KCOs) serve as efficient tools that can adjust cell excitability, and exhibit beneficial effects under pathological conditions such as ischemia, stroke, and neurodegenerative diseases (Yao and Gross, 1994;Sargent et al, 1993;Liss et al, 2005). Emerging evidence including from our laboratory has revealed that the opening of K ATP channels play dominant protective roles in various models of neurodegenerative diseases such as Parkinson's disease (PD) (Tai et al, 2003;Wang et al, 2006;Yang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the pKATP channels has been studied extensively, and consists of multimeric proteins composed of inwardly rectifying-poreforming Kir6.x (Kir6.1/Kir6.2) and regulatorysulfonylurea receptor subunits (SUR1/ SUR/2). The presence pKATP channels in DAergic cells has been demonstrated in several studies (Liss and Roeper, 2001;Liss et al, 2005).…”
Section: Discussionmentioning
confidence: 84%